Highly stretchable hybrid nanomembrane supercapacitors. Issue 29 (4th March 2016) - Kim, Keon Jung; Lee, Jae Ah; Lima, Márcio D.; Baughman, Ray H.; Kim, Seon Jeong
Abstract : A highly stretchable all-solid-state supercapacitor is fabricated by using PEDOT/carbon nanotube sheet hybrid nanomembrane. It exhibited high energy density (7.28–6.87 W h kg −1 ) and stretchability (up to biaxial strain of 600%). Abstract : Supercapacitors that are lightweight, mechanically deformable (stretchable, flexible) and electrochemically stable have potential for various applications like portable, wearable, and implantable electronics. Here we demonstrate a stretchable and high-performing hybrid nanomembrane supercapacitor. The hybrid nanomembrane is prepared by vapour phase polymerization (VPP) based nanoscopic PEDOT coating on carbon nanotube sheets (CNS) transferred onto an elastomeric substrate to form a wavy structure. The resulting wavy structured hybrid nanomembrane based supercapacitor exhibits high electrochemical performance and mechanical stretchability, simultaneously. The high specific capacitances and energy density (82 F g −1, 11 mF cm −2, and 7.28 W h kg −1 at 0% strain) are retained under large mechanical deformation (77 F g −1 and 6.87 W h kg −1 at a biaxial strain of 600%). Moreover, there is only <1% degradation of capacitance ratio after 1000 cycles stretching/releasing and bending/unbending. This high mechanical cyclic stability is shown even during stretching/releasing and bending/unbending measured by dynamic cyclic voltammetry (CV). These results suggest that our supercapacitor is valuable in a wide range of applications that require it to be electrochemically stable under large mechanical deformation, such as strain sensors, wearable electronics and biomedical devices.